The People’s Resistance and Struggle Against Large-Scale Mining in Mindanao - Ordoñez, Rogelio (Social Sciences and Development Review, 2015)
The history of struggle against large-scale mining is as old as when large-scale mining was first introduced on our islands when the Spanish colonialists came in search of gold and spices. As early as the 16th Century, various expeditions were sent to find and wrest the gold mines from the natives. Not  a single Spanish gold mine was established. Of note were those sent to the Cordillera which were repulsed by the indigenous people. High up in the mountains, the Spaniards were no match to the Igorots, the Kalingas and the tribals who fiercely defended their territories and fought invaders. The Lumads of Mindanao also fought against this usurpation of their lands. An example is the uprising of the Kaolo, B’laan, Manobo, Samal and Moro tribes against the colonial landgrabbers. The oral tradition in Mindanao is rich with stories of resistance against the Spanish and American invasion of the islands. These stories serve as landmarks in the people’s continuing march against the invasion of their lands. Thus, gathered here are some of the most celebrated accounts of the peoples’ resistance and struggle against large-scale mining in Mindanao, from the point of view of the victims themselves.
Keywords: People's resistance; Struggle; Large-scale mining; Mindanao